Corporate Social Responsibility in Food and Beverage Industry: An Analysis Study of Soft Drinks Sector in Algeria - Ounane Boumediene; Yahiaoui Nour El Houda (European Scientific Journal, ESJ, 2018)
The aim of this study is to highlight the most important issues of social responsibility for companies in the Algerian beverage sector. In Algeria, despite growing concerns of consumers and health advocates in effects associated with high levels of consumption of beverages on public health, along with other issues such as; the quality of drinks, percentage of sugar, ingredients, packaging. Studies dealing with social responsibility in this sector are rather scarce. Our results show that applying CSR principles stills not very common in this field and too much efforts are needed in order to legitimize the activity of the enterprises, likewise an increasing acceptance of social responsibility principles so that to establish the rules of ethical practices in the future. Finally, some urgent measures, such as installing a good information system as well as a set of laws and standards that regulates CSR, and reducing the effect of the informal sector should be undertaken by the Algerian government.